Ergonomic analysis of a Military Police post in Minas Gerais: A case study - Freitas, Dryelle Rodrigues de (2021)
A large part of the activities performed by military police officers in the exercise of their function has the potential to expose them to ergonomic risks, personal injuries and occupational injuries. In addition to being exposed to a disproportionate physical demand, police officers also refer to tensions that threaten their psychological well-being. This research aims to analyze the workspace of the Military Police in a battalion located in the interior of the state of Minas Gerais, in order to propose solutions for the main points of improvement related to the health and comfort of these professionals. For this,  interviews was used as data collection methods, as well as the use of ergonomic methods Rapid Assessment of the Upper Limb (Rula) and the Nordic Musculoskeletal Questionnaire (NMQ), which allow an effective understanding of the environment to which these inserted professionals and consequently survey of the improved points. As obtained results, important points of improvement were verified, having been made proposals such as the turnover of work shifts in operations, monitoring and psychological support of police officers. In addition, it was proposed to modify the layout to reduce problems with range of movements, as well as to change or adapt part of the furniture and create an awareness program to reduce pain and adverse effects of work.